Toward a semantic-based location tagging news feed system: Constructing a conceptual hierarchy on geographical hashtags. (September 2019) - Davarpour, Mohammad Hossein; Sohrabi, Mohammad Karim; Naderi, Milad
Abstract: Online news and social networking sites have been significantly used in recent years. There has been a lot of efforts to provide appropriate contents for the end users; however, they proved not to be effective. We believe the semantic web (as the third generation of the web) is mature enough to undertake the responsibility of generating more user-centric content. One way to exploit the semantic web's capabilities for such purpose is to construct an ontology that establishes the relationships between hashtags. In this paper, we present the construction process of a news feed system based on the hierarchical relationships of geographic hashtag. Our experiments demonstrated that our proposed semantic-based hierarchical location tagging news feed system increases the quality of the user experience as well as the publication rate of the news while boosting the content match rate to the target audiences. The proposed system of this paper can be considered as a real step towards the realization of semantic web.